2012
DOI: 10.1002/lary.23278
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator modulation by the tobacco smoke toxin acrolein

Abstract: Objectives Evidence indicates that decreased mucociliary clearance (MCC) is a major contributing feature to chronic rhinosinusitis. Tobacco-smoke exposure is thought to inhibit transepithelial Cl− secretion – a major determinant of airway surface liquid hydration and MCC. The objective of the current study was to evaluate the effects of acrolein exposure (a prominent tobacco smoke toxin) on vectorial Cl− transport through the major apical anion channel CFTR in sinonasal epithelium. Study Design In vitro inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 27 publications
3
50
0
Order By: Relevance
“…Aside from direct inhalation via cigarette smoke, acrolein can also be produced through endogenous pathways associated with inflammation (26). Our findings are also supported by studies demonstrating the acute effects of acrolein on CFTR function, albeit at concentrations unlikely to be observed in systemic circulation for sustained periods (37). Acrolein protein modification occurs in the epithelia of patients with COPD and could partially explain persistent decrements in CFTR activity observed due to smoking, because acrolein-protein adducts persist despite prolonged smoking cessation and would be unlikely to be detected in former smokers with COPD (38).…”
Section: Discussionsupporting
confidence: 72%
“…Aside from direct inhalation via cigarette smoke, acrolein can also be produced through endogenous pathways associated with inflammation (26). Our findings are also supported by studies demonstrating the acute effects of acrolein on CFTR function, albeit at concentrations unlikely to be observed in systemic circulation for sustained periods (37). Acrolein protein modification occurs in the epithelia of patients with COPD and could partially explain persistent decrements in CFTR activity observed due to smoking, because acrolein-protein adducts persist despite prolonged smoking cessation and would be unlikely to be detected in former smokers with COPD (38).…”
Section: Discussionsupporting
confidence: 72%
“…Tobacco smoke impacts sinonasal epithelial function, 5457 and several epidemiologic studies have demonstrated that smokers have an increased prevalence of CRS. 58,59 A previous study reported increased biofilm mass in cultures from smokers when the cultures were repetitively exposed to exogenous tobacco smoke, compared to cultures taken from nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study we investigated whether acrolein affects epithelial ion transport and mucin synthesis. In the distal airway, acrolein rapidly alters epithelial ion transport and mucin synthesis in a manner that may indicate reduced airway defenses (Borchers et al 1998; Welsh 1983; Alexander et al 2012). A 60 minute acrolein challenge significantly inhibited cAMP-dependent ion transport.…”
Section: Discussionmentioning
confidence: 99%
“…Acrolein is a byproduct of mobile exhaust, industrial processes, and tobacco smoke (Bein and Leikauf 2011). In the nasal passages, trachea, and lungs, acrolein has a profound and rapid effect on epithelial ion transport and mucin synthesis (Alexander et al 2012; Welsh 1983; Borchers et al 1998; Borchers et al 1999). In excised canine tracheal epithelium and in cultures of sinonasal epithelial cells, exposure to acrolein significantly reduced ion transport within 30 minutes of initial exposure (Welsh 1983; Alexander et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation